Lateral Internal Sphincterotomy versus V-Y Anoplasty in Treatment of Chronic Anal Fissure: a Comparative Trial Based on Manometry Results - Marwa Sobhi; Sameh Hany Emile; Ahmed AbdelMawla; Mohamed Youssef; Sabry Mahmoud (Iranian Journal of Colorectal Research, 2019)
Abstract Background: Conservative treatment of chronic anal fissure (CAF) is the first line of treatment. Patients who fail conservative treatment are offered surgical treatment in the form of lateral internal sphincterotomy (LIS) or V-Y anoplasty.Objective: This prospective study aimed to compare LIS and V-Y anoplasty in the treatment of CAF based on the baseline resting anal pressure of patients.Methods: Female patients with CAF were investigated with anal manometry. Patients with elevated resting anal pressure were treated with LIS and patients with normal or low resting anal pressure were treated with V-Y anoplasty. Data about healing of anal fissure, reduction in pain score, continence disturbance, and complications were recorded on follow-up.Results: Twenty-four female patients of a mean age of 37.6 years were included to this study. Sixteen patients underwent LIS (group I) and 8 underwent V-Y flap (group II). Both groups achieved comparable time to complete healing. Both groups showed significant decrease in pain score at 3 months of follow-up (Group I: 6.1±0.85 to 0.93±0.7, p